Calagem, adubação e nutrição mineral de Anonáceas - Rozane, Danilo Eduardo [UNESP]; Natale, William (Sociedade Brasileira de Fruticultura, 2014)
Among the edaphic factors, those related to acidity are the ones that affect productivity, especially in tropical regions. For culture the Annonaceae, no research results that indicate the proper base saturation, nor the determination of doses, times, application methods and sources of nutrients for orchards Annonaceae in training and production in order to promote sustainability and higher yields. Given the importance and potential of commercial exploitation of Annonaceae in Brazil and, considering the limited available scientific information on liming, fertilization and nutrition of fruit plants of this family, some research has to be carried out urgently due to the effects of nutrients on productivity, fruit quality, post-harvest, tolerance to pests and diseases, etc.

Entre os fatores edáficos, os ligados à acidez são os que mais interferem na produtividade, especialmente nas regiões tropicais. Para a cultura das anonáceas, não há resultados de pesquisa que indiquem a adequada saturação por bases, nem tão pouco a determinação de doses, épocas, modos de aplicação e fontes de nutrientes para pomares de anonáceas em formação e produção, a fim de promover sustentabilidade e elevadas produtividades. Tendo em vista a importância e o potencial de exploração comercial das anonáceas no Brasil e, considerando-se a escassa informação científica disponível sobre calagem, adubação e nutrição dessa família de plantas frutíferas, algumas pesquisas têm urgência de serem realizadas em função dos efeitos dos nutrientes sobre a produtividade, a qualidade dos frutos, a pós-colheita, a tolerância a pragas e doenças e, etc.
Liming, fertilizer and mineral nutrition of Annonaceae
Keywords: Annona spp.; lime; Soil acidity; Fertilizer; Plant nutrition; Annona spp.; Calcário; Solos - Acidez; Adubo; nutrição de plantas